Preparation and Characterisation of Polypyrrole-Iron Oxyhydroxide Nanocomposite as Sensing Material. (14th December 2020) - Diauudin, Farah Nabila; Mohd Noor, Siti Aminah; Abdul Rashid, Jahwarhar Izuan; Feizal Knight, Victor; Wan Yunus, Wan Md Zin; Ong, Keat Khim; Mohd Kasim, Noor Azilah; Taufik, Safura; Samsuri, Alinda; Shamsudin, Intan Juliana; Latip, Wahhida
Abstract : Polypyrrole (PPy) has been widely used as a sensing material in many studies as PPy gives out noticeable reactions towards varieties of vapours of acids, bases, alcohols, alkanes, and chemical warfare agent (CWA) simulants. However, due to dispersion and mechanical properties limitation, PPy in nanoparticles (PPy NPs) has been introduced. The combinations between PPy NPs and nanosized metal oxide have shown promising improvement in the sensitivity of a sensor due to the larger total surface area of detection. In this study, the potential of PPy NPs and polypyrrole-iron oxyhydroxide (PFFs) nanocomposite as sensing materials in detecting the CWA simulant, dimethyl methylphosphonate (DMMP), is investigated. PPy NPs and modified PFFs nanocomposite were successfully synthesised using chemical oxidative polymerisation. The formation of PPy NPs and the effect of iron-oxyhydroxide (FeOOH) on the chemical interaction, morphology, and size of PPy NPs were investigated using attenuated total reflection-Fourier transform infrared (ATR-FTIR), field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM). ATR-FTIR analysis showed that the modified PFFs nanocomposite was successfully produced through the presence of a sharp –OH peak. The size of the prepared PPy NPs and PFFs nanocomposite was observed in the range of 50 to 70 nm and 110 to 160 nm, respectively, through TEM analysis. The electrochemical behaviour of PPy NPs and PFFs nanocomposite towards DMMP was investigated using cyclic voltammetry (CV) where, in the presence of DMMP, PPy NPs and PFFs nanocomposite showed 24% and 21% current signal reduction, respectively. This suggests that both PPy NPs and PFFs nanocomposite are able to discriminate an electrical signal both with and without the presence of DMMP.